2020
DOI: 10.1017/s0029665120001834
|View full text |Cite
|
Sign up to set email alerts
|

Brain macroautophagy on the ketogenic diet

Abstract: AbstractThe ketogenic diet has been shown to be very effective in managing drug-resistant epilepsy, treatment of obesity, improving symptoms of diabetes and reducing cardiovascular risk. Growing evidence supports the use of the ketogenic diet as an alternative or additional therapy in many types of cancer, polycystic ovary syndrome, acne, and neurological diseases. The rationale for the use of the ketogenic diet in brain diseases is based on its neuroprotective properties. But … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…It was observed that a ketogenic diet upregulated hepatic autophagy in mice [96]. The same authors showed that the ketogenic diet upregulated the autophagosome-associated protein LC3-II in mouse hippocampal and cerebrocortical samples [97]. In general, these studies confirmed further research showing that ketosis may promote brain autophagy by activating Sirtuin 1 and hypoxia-inducible factor-1 [98].…”
Section: The Ketogenic Diet and Ketone Bodies In Agingmentioning
confidence: 62%
“…It was observed that a ketogenic diet upregulated hepatic autophagy in mice [96]. The same authors showed that the ketogenic diet upregulated the autophagosome-associated protein LC3-II in mouse hippocampal and cerebrocortical samples [97]. In general, these studies confirmed further research showing that ketosis may promote brain autophagy by activating Sirtuin 1 and hypoxia-inducible factor-1 [98].…”
Section: The Ketogenic Diet and Ketone Bodies In Agingmentioning
confidence: 62%
“…Ketogenic diet (KD) is a high‐fat and low‐carbohydrate diet that can lead to nutritional ketosis and has been used to treat refractory epilepsy 8 . Evidence has showed that the use of the KD has been an alternative or additional therapy in variety of cancers, PCOS, neurological diseases, and acne 9 . Mavropoulos et al have reported that KD significantly improved the body weight, LH/FSH ratio, and fasting insulin in patients with PCOS and obesity 10 .…”
Section: Introductionmentioning
confidence: 99%